Low prevalence of mobilized resistance genes blaNDM, mcr-1, and tet(X4) in Escherichia coli from a hospital in China - Sun, Lin; Sun, Guo-Zhuang; Jiang, Yue; Mei, Cai-Yue; Wang, Zhen-Yu; Wang, Han-Yun; Kong, Gui-Mei; Jiao, Xinan; Wang, Jing (Frontiers in Microbiology, 2023)
The emergence and spread of carbapenemase genes, colistin resistance genes mcr-1, and tigecycline resistance gene tet(X) represent a significant threat to clinical therapy and public health. In this study, we investigated the presence of carbapenemase genes, mcr-1, and tet(X) in 298 Escherichia coli strains obtained from a teaching hospital in China. Eight (2.68%), six (2.01%), and one (0.34%) E. coli isolates carried blaNDM, mcr-1, and tet(X4), respectively. The blaNDM gene was located on IncX3 (n=4), F2:A-:B- (n=3), and F2:A1:B1 (n=1) plasmids, with high similarity to multiple plasmids belonging to the same incompatibility type from Enterobacteriaceae. Six MCR-producing strains contained mcr-1-carrying IncI2 plasmids, organized similarly to other mcr-1-bearing IncI2 plasmids from animals in China. The blaCTX-M-55/64/132/199 gene located within a typical transposition unit (ISEcp1-blaCTX-M-orf477∆) was inserted near dnaJ to generate 5-bp direct repeats in four mcr-1-positive plasmids. The tet(X) and another four resistance genes [aadA2, tet(A), floR, ∆lnu(F)] were co-located on an IncX1 plasmid, highly similar to other tet(X4)-carrying IncX1 plasmids from Escherichia and Klebsiella of animal or food origin, except that conjugative transfer region of IncX1 plasmids was absent in our plasmid. Although a low prevalence of blaNDM, mcr-1, tet(X) was observed in E. coli from patients in this study, their dissemination associated with some successful pandemic plasmids is of great concern. Continued surveillance of these crucial resistance genes in patients should be strengthened.